Review on iron regulatory hormone Hepcidin - V.P, Pathmashri.; Sethu, Gowri; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
To study a review on the iron-regulating hormone hepcidin. Hepcidin is a major regulator of iron metabolism. This review is done on hepcidin and its role in the regulation of iron in our body. Hepcidin is a 25-amino acid peptide that is synthesized in hepatocytes. Liver-derived hepcidin peptide is secreted in response to iron and inflammation and interacts with the iron export protein ferroprotein. Hepcidin can control both the total body iron by modulating intestinal iron absorption as well as promote iron available for erythropoiesis by affecting the efficiency with which macrophages recycle iron from red blood cells. This review will give information about the hormone hepcidin and the regulation of iron in the human body.